Peluang Bisnis Cangkang Telur bagi Ibu Rumah Tangga - Mardhiah, Ainal; Hayati, Rahmah; Wardani, Sari; Mulyadi; Yeni, Elfa; Handayani, Lia; Maulidya, Rulita; Meliyana; Isfanda (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
The potential for the development of eggshells into a product has not been looked at by the public so that the egg waste produced is considered as useless waste. The egg cang business into organic fertilizer can be a promising opportunity to be developed. The lack of public knowledge to manage eggshells makes egg shells simply thrown away without being used as a product with economic value. Socialization activities for eggshell business opportunities can foster the interest of housewives to start a business derived from eggshell waste. The high enthusiasm of housewives in participating in every stage of fertilizer making comes from egg shells to the packaging process. Marketing is one of the obstacles because this eggshell fertilizer product can only be marketed in Lamnga Village, Aceh Besar.